The Effects of the Solution-Focused Model on Anxiety and Postpartum Depression in Nulliparous Pregnant Women - Huang, Cuiqin; Han, Wei; Hu, Sanlian (Frontiers in Psychology, 2022)
Background: Solution-focused model (SFM) is an intervention method that fully mobilizes patients’ initiative through their potential. We aimed to investigate the effects of SFM on anxiety and postpartum depression in nulliparous pregnant women compared with routine care services. Methods: We chose the mothers diagnosed as depressed or with depressive tendency by EPDS at 28 weeks of gestation and divided them into the intervention and control groups. The control group only took the routine pregnancy healthy nursing, while the SFM group took the regular nursing and SFM counselling. Different assessments were conducted at 28 weeks of gestation, post-delivery and post-intervention to evaluate the anxiety and depression levels of the patients. Finally, nursing satisfaction was evaluated by the nursing satisfaction questionnaire. Results: Compared with the control group, SFM could decrease the scores of anxiety and depression more effectively and influence sleep quality more positively. We also found that SFM resulted in significantly higher nursing satisfaction than that in the control group (p=0.0046) Conclusion: In conclusion, SFM could effectively alleviate anxiety and postpartum depression in nulliparous pregnant women.